Optical‐Mode Structure of Micropillar Microcavities Containing a Fluorescent Conjugated Polymer. Issue 2 (4th November 2019) - Al‐Jashaam, Faleh L.; Jayaprakash, Rahul; Coles, David M.; Musser, Andrew J.; Georgiou, Kyriacos; Lidzey, David G.
Abstract: The light emission from a series of micropillar microcavities containing a fluorescent, red‐emitting conjugated polymer, is explored. Cavities are fabricated by defining two dielectric mirrors either side of a polymer active region. Focused ion‐beam (FIB) lithography is then used to etch pillar structures into the planar cavity having diameters between 1 and 11 µm. The photoluminescence (PL) emission of the cavities is characterized using real‐space tomographic and Fourier‐space imaging techniques, with emission shown to be quantized into a mode‐structure resulting from both vertical and lateral optical confinement within the pillar. The optical‐confinement effects which result in a blue‐shift of the fundamental mode as the pillar diameter is reduced is demonstrated, with a model applied to describe the energy and distribution of the confined optical modes. Abstract : Researchers from the University of Sheffield fabricate micropillars containing a red‐emitting conjugated polymer, and use advanced imaging techniques to demonstrate mode quantization arising from lateral confinement. Such low mode volume, high quality factor micropillars are a step forward toward the observation of macroscopic quantum phenomena such as condensation and superfluidity or even as single‐photon sources.